New barriers hinder African trade - Gumisai Mutume (Africa Renewal, 2006)
Just as developing countries are beginning to overcome some major hurdles in their quest to expand trade with industrial countries, another is rearing its head. As a result of agreements negotiated at the World Trade Organization (WTO), traditional trade protection measures such as tariffs and quotas are falling away. But to some extent they are being replaced by domestic technical regulations that permit countries to bar products from entering phytosanitary rules, further limit goods” exported to the Organization for Economic Cooperation and Development (OECD), a grouping of 30 wealthy nations.